Christian ethics : contemporary issues & options - Geisler, Norman L. (Grand Rapids, Mich. : Baker Academic, 2010)
"In this thorough update of a classic textbook, noted Christian thinker Norman Geisler evaluates contemporary ethical options (such as antinomianism, situation ethics, and legalism) and pressing issues of the day (such as euthanasia, homosexuality, and divorce) from a biblical perspective. The second edition is significantly expanded and updated, with new material and charts throughout the book. There are new chapters on animal rights, sexual ethics, and the biblical basis for ethical decisions, as well as four new appendixes addressing drugs, gambling, pornography, and birth control. The author has significantly updated his discussion of abortion, biomedical ethics, war, and ecology and has expanded the selected readings, bibliography, and glossary" -- Publisher description.
Part 1. Ethical Options: All the options -- Antinomianism -- Situationism -- Generalism -- Unqualified absolutism -- Conflicting absolutism -- Graded absolutism -- The basis for ethical decisions -- Part 2. Ethical Issues: Abortion -- Infanticide and euthanasia -- Biomedical issues -- Capital punishment -- War -- Civil disobedience -- Sexual issues -- Homosexuality -- Marriage and divorce -- Ecology -- Animal rights.
Includes bibliographical references and indexes.
Keywords: Christian ethics